Zircon U-Pb ages of debris from the basal ice of the Byrd ice core, central West Antarctica ... - Thomson, Stuart; Marschalek, James; Licht, Kathy (Zenodo, 2023)
This dataset comprises of 16 zircon U-Pb ages. Zircon grains were picked out of the 75-150 micron size fraction of debris melted from two intervals of basal ice from the Byrd ice core. The Byrd ice core was drilled at 80° 0.1'S, 119° 31.0'W at Byrd Station, West Antarctica, in January 1968. ...